2003
DOI: 10.1063/1.1554271
|View full text |Cite
|
Sign up to set email alerts
|

Potential energy functions of the X̃ 2B1, Ã 2B2, B̃ 2A1, and C̃ 2A2 states of Cl2O+ and the X̃ 1A1 state of Cl2O: Franck–Condon simulations of photoelectron bands of Cl2O which include anharmonicity

Abstract: Restricted-spin coupled-cluster single and double plus perturbative triple excitations ͓RCCSD ͑T͔͒ and/or complete-active-space self-consistent-field multireference internally-contracted configuration interaction ͑CASSCF/MRCI͒ potential energy functions of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Subsequently, the HeI photoelectron spectrum of Cl 2 O was reinvestigated by Chau et al through computing Franck-Condon factors based on the ab initio data, in which the anharmonicity was introduced in the calculations. 18 It was found that the first, second and fourth bands were consistent with the experimental envelope. In particular, the first and second bands were in better agreement with experiment than the results from earlier harmonic IFCA calculations.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…Subsequently, the HeI photoelectron spectrum of Cl 2 O was reinvestigated by Chau et al through computing Franck-Condon factors based on the ab initio data, in which the anharmonicity was introduced in the calculations. 18 It was found that the first, second and fourth bands were consistent with the experimental envelope. In particular, the first and second bands were in better agreement with experiment than the results from earlier harmonic IFCA calculations.…”
Section: Introductionsupporting
confidence: 63%
“…Table 2 lists the equilibrium geometrical parameters and harmonic frequencies of the ground state for neutral Cl 2 O(X ˜1A 1 ), and vertical ionization energies (VIEs) of the four lowest cationic states, together with previous theoretical results, [17][18][19] and available experimental data 4,5,23,24 for comparison. It can be seen that the geometries obtained at the RCCSD(T)-F12 and MRCI-F12+Q levels with the cc-pCVXZ-F12(X = D, T, Q) basis set are consistent with each other and in good accord with the experimental results.…”
Section: A Tests Of the Ab Initio Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Photochemistry and photophysics of Cl 2 O have recently received considerable attention for several reasons. The photochemistry of chlorine oxides is of general interest due to their role in atmospheric chemistry, although Cl 2 O does not directly take part in the ozone depletion process in the stratosphere. Discrepancies in the assignment of its excited electronic states , exist, as well as disagreement between experimental and theoretical data with respect to its dissociation dynamics, ,, both of which have not completely been resolved until now.…”
Section: Introductionmentioning
confidence: 99%